Fiscal Decentralisation, Democratic Institutions and Inflation (The Pakistan Development Review, 2013)
This study examines the role of democratic institutions in an attempt to explain the relationship between fiscal decentralisation and inflation. The empirical analysis is based on time series data over 1972–2010 for Pakistan using the GMM estimation procedure. Three different measures of fiscal decentralisation are used in order to capture multidimensionality. The major findings of the study suggest that expenditure decentralisation has a negative impact on inflation if accompanied by democratic institutions. Revenue decentralisation, however, has a negative impact on inflation even in the absence of institutions, though institutions accentuate this effect. The role of institutions, therefore, is important in realising the benefits of fiscal decentralisation. Composite decentralisation has a negative and significant impact on inflation. This implies that expenditure decentralisation becomes effective when it is complemented with revenue decentralisation. Intuitively, provincial governments become more responsive when their expenditure needs are met with their own revenues. JEL Classification: E31, H11, H72 Keywords: Fiscal Decentralisation, Inflation, Institutions, Pakistan